Sosialisasi Penguatan Pembelajaran dan Asesemen Kurikulum Merdeka - chika rahayu; Reza Lestari; Irma Sendy Aristya; Yoga Pratama; Fadilaturrahmah Fadilaturrahmah; Lisnani Lisnani; B.A. Indriasari; Tresiana Sari Diah Utami; Agustinus Riyanto; Anastasia Sri Sukistini; Nuryani Nuryani (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
This topic was chosen because of the need of the school to improve understanding about the implementation of the merdeka curriculum in learning and assessment. This service aims to assist participants in enhancing their understanding of the merdeka curriculum in learning and assessment. The implementation method is conducted online through Zoom using lectures, discussions, and Question Asking sessions. The results of this activity have had a positive impact on the participants' understanding of independent curriculum planning and assessment, as demonstrated by the comparison between their initial understanding using Jamboard media questions and their final understanding using Padlet media reflection questions at the end of the activity.